Maintenance Service Cost Emphasize Dump Truck Volvo FMX 440 at PT Iwaco Jaya Abadi Site Kideco - Wahyu Mutiara Ramadhan; Anis Siti Nurrohkayati (Universitas Muhammadiyah Sidoarjo, 2022)
Maintenance is a series of activities to keep facilities and equipment in a ready-to-use state to carry out production effectively and efficiently according to a predetermined schedule and based on standards. In this research, the author emphasizes the cost of maintenance service and the use of Petronas SAE 15W-40 engine oil on the VOLVO FMX 440, Dump truck unit, which is carried out according to service intervals, namely every 250, 500, 1000, and 2000 hours. The research method used is preventive maintenance which in this method prevents damage to the unit in operation by scheduling routine maintenance. In this method, replace components so that the unit's life can be longer, and minimize damage. This study aims to emphasize the cost of replacing and using Petronas SAE 15W-40 engine oil on the VOLVO FMX 440 Dump Truck unit which is claimed to last up to 500 hours of operation, so that engine oil changes in 250 hours and 750 hours do not need to be replaced with engine oil, but by replacing the Oil engine every 500 hours of operation, it can save service costs which initially amounted to Rp. 639,104,145.00/year to Rp. 578,472,585.00/year, and for the use of an oil engine in one year which was initially Rp. 126.755,080.00 /year to only Rp66,143,520.00/year.